Senior brain - the influence of life experience on cognitive functions - Aldona Molęda (Nofer Institute of Occupational Medicine, 2024)
Time-related ageing of the organism brings about the limitations to all human beings. The ageing process pertains to all organs and neither does it spare the brain, although, apart from neurodegenerative diseases, the changes in brain's functions seem to be less detectable. Many studies that were conducted for years in ageing adults provide evidence that lifestyle in which psychic and physical activity is maintained significantly and positively affects brain plasticity, i.e., normal ability to learn and develop, and therefore this lifestyle serves as a protective agent for cognitive functions even in the case of degenerative changes of brain tissue. Med Pr Work Health Saf. 2024;75(3):279-285